Death and dying in a Karen refugee community: An overlooked challenge in the resettlement process. (December 2019) - Bird, Jessica Nancy
This paper explores death and dying in a settling refugee community. I use ethnographic description to explore an overlooked practical challenge of resettlement – funerals. The focus of research is the Brisbane Karen community, from Burma and/or Thai-Burma border camps. Death and dying as a theme of resettlement research is inadequate. Yet we ought to consider death and dying as a settlement challenge, just as we consider language, employment, or housing (for example). Death and dying traverses the practical challenges of settlement, to deeper ontological questions associated with spiritual existence, rituals and community bonding. The paper provides practical insights into the basic boundaries of Australian funeral practice, which can speak to other minority groups practising burial rites that depart from the mainstream. It comments on how those boundaries can bump up against cultural practice brought from elsewhere. It also demonstrates transnationalism in the Brisbane Karen community.